Comparison of posttherapy 90Y positron emission tomography/computed tomography dosimetry methods in liver therapy with 90Y microspheres - Knesaurek, Karin (World Journal of Nuclear Medicine, 2020)
The aim of our study was to compare dosimetry methods for yttrium-90 (90Y) positron emission tomography/computed tomography (PET/CT). Twenty-five patients were taken to a PET/CT suite following therapy with 90Y microspheres. The low mA, nondiagnostic CT images were used for attenuation correction and localization of the 90Y microspheres. The acquisition time was 15 min, the reconstruction matrix size was 200 mm × 200 mm × 75 mm, and voxel size was 4.07 mm × 4.07 mm × 3.00 mm. Two software packages, MIM 6.8 and Planet Dose, were utilized to calculate 90Y dosimetry. Three methods were used for voxel-based dosimetry calculations: the local deposition method (LDM), LDM with scaling (LDMwS) for known injected activity, and a dose point kernel (DPK) method using the MIRD kernel. Only the DPK approach was applied to the Planet Dose software. LDM and LDMwS were only applied to the MIM software. The average total liver dosimetry values (mean ± standard deviation) were 60.93 ± 28.62 Gy, 53.59 ± 23.47 Gy, 55.33 ± 24.80 Gy, and 54.25 ± 23.70 Gy for LDMwS, LDM, DPK with MIM, and DPK with Planet Dose (DOSI), respectively. In most cases, the LDMwS method produced slightly higher dosimetry values than the other methods. The MIM and Planet Dose DPK dosimetry values (i.e., DPK vs. DOSI) were highly comparable. Bland–Altman analysis calculated a mean difference of 1.1 ± 2.2 Gy. The repeatability coefficient was 4.4 (7.9% of the mean). The MIM and Planet Dose DPK dosimetry values were practically interchangeable. 90Y dosimetry values obtained by all methods were similar, but LDMwS tended to produce slightly higher values.
Keywords: 90Y dosimetry; 90Y microspheres; hepatocellular carcinoma